Karakterisasi sifat kuantitatif dan sifat kualitatif dua puluh satu genotipe melon (Cucumis melo L.) - Kuhesa, Rova Endang; Parwito, Parwito; Sari, Dia Novita (PendIPA Journal of Science Education, 2024)
In the last three years, the production of melon has decreased. The decline in melon production was caused by the limited availability of superior seed varieties. Therefore, increasing production by developing superior varieties with high yields is necessary. Characterization is the first step in breeding plants. The research objective was to determine the characteristics of 21 melon genotypes. The research was conducted from January to March 2024. The research was conducted in Lubuk Saung Village, North Bengkulu Regency, Bengkulu Province. The experiment used a randomized complete block design on one factor with three replications. The factors used were 21 melon genotypes. The results showed that cluster analysis with a similarity of 33.33 produced five groups of melons, and G15 was the most different genotype among the other genotypes. Medium leaf size and medium green leaf color are the most dominant sizes and colors. The length of the leaf lobes in the medium category and the development of the leaf lobes in the weak category are the most dominant. The round shape of the fruit is the most common form of fruit. The skin color of the fruit before it is ripe is most green, and the color of the flesh when it is ripe is most white. Fruit without grooves is the most dominant, and surface wrinkles in the fragile fruit are the most dominant. Based on the characterization results, the next stage is selecting new superior varieties according to the desired characteristics.